If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3d + -8.1 = 6.33 Reorder the terms: -8.1 + 3d = 6.33 Solving -8.1 + 3d = 6.33 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '8.1' to each side of the equation. -8.1 + 8.1 + 3d = 6.33 + 8.1 Combine like terms: -8.1 + 8.1 = 0.0 0.0 + 3d = 6.33 + 8.1 3d = 6.33 + 8.1 Combine like terms: 6.33 + 8.1 = 14.43 3d = 14.43 Divide each side by '3'. d = 4.81 Simplifying d = 4.81
| 8.68=2s-11.1 | | 24-4x=2x-18 | | a(2b+3c)= | | 6v^2-23+10=0 | | -6x-12=6x+8 | | -4z(z-7)=0 | | -4(3-7x)= | | 6+2y=12.2 | | -6x-12=3x+8 | | 3y-2=2.26 | | 3(x+5)-2x+12= | | 7(314)-75(21)-2(259)=x(10+5) | | -2.22=m/4-5 | | 3[z-(6z+15)+5]=3(z+2) | | 1.3+2.3=2.3-2.3 | | Y+6+y=28 | | 7(314)-75(21)-2(259)=x(3+5) | | 1.2=4s-11.2 | | -7(x-8)=9-6x | | 11w-81=744 | | -8-5n=64+3 | | -2y^2-14y+7=0 | | 8[5-8(x-1)]+7[(5x+6)-8]=11x-341 | | .8=ln(y) | | 0=x^2+2x-63 | | 4x+4x=7x-9 | | 5y(y-2)=6-3y | | 4.7x+2=3.2x-4 | | 40x+4(1.5x)=736 | | 4(x-6)-(x+2)=-12 | | g/6-17=1 | | 4x-3+2=8x-3-x |